Improving Mathematics Learning Outcomes With The Application of Cooperative Learning Model For XII MIPA of SMAN 8 Takalar - Fatwa, Inayanti; Harjuna, Hariani (EduLine: Journal of Education and Learning Innovation, 2021)
This research is a Classroom Action Research (CAR) which aims to determine the improvement of mathematics learning outcomes with specialization by applying the cooperative learning model of class XII MIPA students at SMAN 8 Takalar. From the results of this study, it can be seen the percentage of classical completeness from the initial test (pre-test), cycle I, and cycle II. In the initial test before getting the cooperative learning model treatment on specialization mathematics subjects, the average score of the student learning outcomes test reached 60.21. Furthermore, in the first cycle learning outcomes test increased to 71.39. This means an increase of 11.18. Then in the second cycle of learning outcomes test, the average value of the class reached 78.12. This means that there is an increase of 6.73 from cycle I. Before the action treatment was held, the number of students who achieved the minimum completeness criteria indicator (KKM) namely â‰¥72 was 14 students or 42.42%, while seen from the activities of the first cycle the number of students who achieve the KKM score increased to 20 students or 60.60%. The increase was also seen in the second cycle, the number of students who achieved the KKM score was 26 students or 78.78%.